Effect of Solid- State Fermentation Biomass Supplementation to Mixed Substrate on Digestibility and Methane Mitigation in vitro - Patel, Kishan P.; Katole, Shrikant B.; Pandya, P. R.; Sorathia, K. K.; Patel, Srushti (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to assess the effect of supplementation of various levels of solid-state fermentation (SSF) biomass on in vitro digestibility, total gas production and methane production. Eight different types of substrates were prepared viz. SSF0 (control), and the basal substrates supplemented with SSF biomass at 1%, 2%, 3%, 4%, 5%, 6% and 7% replacing mixed cereal straw was designated as SSF1, SSF2, SSF3, SSF4, SSF5, SSF6 and SSF7, respectively. In vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD) were 10.62 and 11.70% higher (P